An overview of audiovisual translation: Four methodological turns in a mature discipline - Chaume, Frederic (Journal of Audiovisual Translation, 2018)
Digital technology has played a crucial role not only in the process of production and distribution of audiovisual content, but also in the process of localization and consumption of audiovisual products. This has had an obvious impact on audiovisual translation as a field, both in professional circles as well as in scholarly research. To date, this field of research has grown exponentially, parallel to the production, consumption, interaction with and general interest in audiovisual products. At the same time, translation studies have been growing as a discipline and, consequently, has been influencing audiovisual translation (AVT) research. This article presents a due brief overview of the four turns audiovisual translation has taken to date (the descriptive, the cultural, the sociological and the cognitive turns), and identifies some of the major steps already undertaken, as well as possible research avenues that such turns are currently opening.